Pathophysiology of mesenteric ischemia/reperfusion: a review. - Cerqueira, Nereide Freire; Hussni, Carlos Alberto [UNESP]; Yoshida, Winston Bonetti (FapUNIFESP (SciELO), 2005)
During ischemia, the cell structures are progressively damaged, but restoration of the blood flow, paradoxically, intensifies the lesions caused by the ischemia. The mechanisms of ischemia injury and reperfusion (I/R) have not been completely defined and many studies have been realized in an attempt to find an ideal therapy for mesenteric I/R. The occlusion and reperfusion of the splanchnic arteries provokes local and systemic alterations principally derived from the release of cytotoxic substances and the interaction between neutrophils and endothelial cells. Substances involved in the process are discussed in the present review, like oxygen-derived free radicals, nitric oxide, transcription factors, complement system, serotonin and pancreatic proteases. The mechanisms of apoptosis, alterations in other organs, therapeutic and evaluation methods are also discussed.
Keywords: reactive oxygen metabolite; human; intestine; ischemia; mesentery; pathology; pathophysiology; peritoneal disease; reperfusion injury; review; vascularization; Humans; Intestines; Ischemia; Mesentery; Peritoneal Diseases; Reactive Oxygen Species; Reperfusion Injury